Maqashid Syariad Asy-Syatibi Review of Marital Rape in the Sexual Violence Crime Law - Zulfikar, Faisal; Taqiyuddin, Hilman; Muchlisin, Mohamad (Universitas Islam Negeri Raden Fatah Palembang, 2023)
In today's life, there are many cases that we often hear about or see that are directly or indirectly related to external sexual violence or marital rape. Therefore it is necessary to formulate rules that can reduce the number of violence, especially marital rape which is a concern for everyone to get married. Maqosid Syariah is one of the appropriate alternative sources of law originating from sources of Islamic law. The following research is a qualitative descriptive research equipped with library research methods with a normative juridical approach. The formulation for regulation of domestic violence in Law Number 12 of 2022 concerning the Law on Sexual Violence has fulfilled the dharuriyat category or primary needs in Maqashid Syariah related to kulliyat al khams, one of the main things, namely Hifzu al-nafs (life protection). In this position, the Act on Sexual Violence can use Maqashid Syariah as an alternative point of view. By formulating these regulations, the concept of Maqashid Syariah can be used for the purpose of common interest has been implemented. With regulations like this, it can be a benchmark for reducing domestic violence.